Factors of the Use of E-learning during COVID-19 Lockdown among the College Students of Nepal: A Cross-Sectional Study - Poonam Pokhrel Sapkota; Dr. Shyam Prasad Sedai; Megha Raj Sapkota (Journal of Balkumari College, 2022)
Background: COVID-19 Pandemic had affected all sectors of human life around the globe. Education is one of them where traditional method of teaching had to be shift to virtual learning all of sudden in both developed and developing countries. Therefore, the article reflects the associated factors of E-learning among college students of Nepal during emergency shift of teaching paradigm due to COVID -19. Methodology: Convenient sampling method through social media and Google form was used to collect 385 data from college students of Nepal during COVID-19 lockdown. Results: The result showed that only 30% of the Nepalese students had all the required resources all the time for the use of E-learning however, 85% of the student had engaged in in E-learning during COVID-19 pandemic lockdown. The study found that gender, marital status, training on the use of E-learning, experience of E-learning prior to pandemic were statistically significant with the future use of E-learning. Conclusions: Educational institutions need be responsive towards the challenges faced by students during E learning, so that learning needs of the students will be fulfilled even in pandemic situation.